Geospatial and Image Data from the "When Computers Dream of Charcoal: Using Deep Learning, Open Tools and Open Data to Identify Relict Charcoal Hearths in and Around State Game Lands in Pennsylvania" Paper. (5th November 2021) - Conner, Weston; Carter, Benjamin; Blackadar, Jeff
These data were used to build an object detection model to locate Relict Charcoal Hearths (RCH) as described in the paper "When Computers Dream of Charcoal: Using Deep Learning, Open Tools and Open Data to Identify Relict Charcoal Hearths in and around State Game Lands in Pennsylvania" [1 ]. This is the first grouping of data for the paper above. The second grouping is also available in this journal, see "Object detection model, image data and results from the "When Computers Dream of Charcoal: Using Deep Learning, Open Tools and Open Data to Identify Relict Charcoal Hearths in and around State Game Lands in Pennsylvania" paper". These files consist of georeferenced Digital Elevation Model, Hillshade and Slope files derived from LiDAR for the State Game Lands (SGL). Included is a Shapefile and GeoJSON of State Game Land borders as well as the program used for downloading the LiDAR files. These data are stored on Zenodo.org .